RELEVANSI PROGRAM 7 KEBIASAAN ANAK INDONESIA HEBAT DALAM PERSPEKTIF FILSAFAT PENDIDIKAN DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW 2016-2026 - Nur Hanifah; Albita Intan Viola; Dwi Amalia Nur Chasanah; Reninda Lindu Astuti; Angelica Aninda Maylanie; Taufik Muhtarom (STKIP Subang, 2026)
This study aims to analyse: (1) the relationship between the philosophical concepts of idealism, realism, pragmatism and progressivism and the values in the ‘7 Habits of Great Indonesian Children’ programme; (2) the philosophical relevance of this programme in strengthening pupils’ character and moral values in the digital age; and (3) implementation strategies recommended in the literature as solutions for character education in primary schools. The study employs a qualitative approach using the Systematic Literature Review (SLR) method in accordance with the PRISMA guidelines. Inclusion criteria comprise articles published between 2021 and 2026, published in Sinta 1–6 indexed journals, utilising either qualitative or quantitative research methods, and focusing on the primary school level. Exclusion criteria included articles published before 2021, those not published in Sinta 1–6-indexed journals, those not using the SLR method, and those discussing lower secondary, upper secondary, or higher education levels. Based on the selection process in accordance with these criteria, 31 articles were identified for review. The results of the study indicate that the ‘7 Habits of Great Indonesian Children’ Programme aligns with the principles of idealism in moral development, realism in learning based on real-life experiences, pragmatism through practical habit-forming, and progressivism in the development of pupils’ potential. This programme is of urgent importance in strengthening character in the digital age and is recommended for implementation through habit-forming.